Practical foundations of an operational guide model for the functioning of municipal school coexistence committees - Lozada-Ballesteros, Yeny Carolina; Barrios-Galvis, Sonia Paola (DIXI, 2024)
The research presents an analysis of the operation of the Municipal School Coexistence Committees that in Colombia were classified as national referents by the Ministry of National Education, based on the direct observation of focus groups, semi-structured interviews, and pronouncements of the territorial entities certified in 2021, and presented practical foundations for an operational guide model to guide their operation. The research was qualitative, with a socio-legal approach. The main results critically express the practical foundations for the formulation of an operational guide model for the functioning of the Municipal School Coexistence Committees, which provides clarity in terms of its formation, operation, and evaluation process, in order to strengthen the school coexistence system of the territorial entities and maximize its impact on the actions within the elementary and middle school educational establishments.